SUBJEK PENDIDIKAN DALAM KAJIAN TAFSIR SURAT AL-ANFAL AYAT 27 - Hafid (Qolamuna : Jurnal Studi Islam, 2021)
In this article, the focus is on discussing and examining theterminology of the subject of education in terms, objectives andcontent or educational material in the perspective of the Qur'an.Descriptive approaches and library research related to the subject ofeducation in the perspective of the Qur'an include Imaniyah,khuluqiyyah, Jismiyah, Al-aqliyah wa al nafsiyah and Almihna. TheQur'an expresses the term education with the words tarbiyah andtaklim. The content in the letter al-Anfal verse 27 teaches that theprincipal is a mandate from Allah SWT given to humans. As the headof the school, the principal has the task of managing various affairs inthe school. Schools as formal institutions managed by the governmentand the community are the most likely places for a person. Keywords: Subject, Education, Q.S An-Nahl.